Despite Cultures : Early Soviet Rule in Tajikistan - Kassymbekova, Botakoz (Book collections on Project MUSE., 2016)
"Despite Cultures examines the strategies and realities of the Soviet state-building project in Tajikistan during the 1920s and 1930s. As Kassymbekova reveals, the local ruling system was built upon an intricate network of individuals, whose stated loyalty to communism was monitored through a chain of command that stretched from Moscow through Tashkent to Dushanbe/Stalinabad"--Provided by publisher.